Genetic studies of human neuropathic pain conditions: a review. Issue 3 (March 2018) - Zorina-Lichtenwalter, Katerina; Parisien, Marc; Diatchenko, Luda
Abstract : Abstract: Numerous studies have shown associations between genetic variants and neuropathic pain disorders. Rare monogenic disorders are caused by mutations of substantial effect size in a single gene, whereas common disorders are likely to have a contribution from multiple genetic variants of mild effect size, representing different biological pathways. In this review, we survey the reported genetic contributors to neuropathic pain and submit them for validation in a 150, 000-participant sample of the U.K. Biobank cohort. Successfully replicated association with a neuropathic pain construct for 2 variants in IL10 underscores the importance of neuroimmune interactions, whereas genome-wide significant association with low back pain ( P = 1.3e-8) and false discovery rate 5% significant associations with hip, knee, and neck pain for variant rs7734804 upstream of the MAT2B gene provide evidence of shared contributing mechanisms to overlapping pain conditions at the molecular genetic level. Abstract : A comprehensive overview of published associations between genetic variants and human neuropathic pain conditions with validation of reported findings in the U.K. Biobank.